Afro-Ecuadorian Ethnoeducation. A literature review - Haro Chávez, Yadira; Ortiz Huera, Omar (Revista Ecos de la Academia, 2024)
The Afro-Ecuadorian Ethno-Education is an innovative proposal that assists in the development of a teaching and learning process with cultural relevance for the Afro-people. The study focused on analyzing the conceptions, perspectives, and challenges of the implementation of the ethno-educational program among Afro-Ecuadorian populations. The research is documentary-type, which allowed the review and analysis of different bibliographic sources about Afro-Ecuadorian ethno-education and its implementation in the educational field. As relevant results, the importance of the development of the ethno-educational proposal from the “home inside” conception in “Guardianas de los Saberes” institutions and other surrounding areas with a larger Afro population is highlighted. Since it favors the recognition and appreciation of ancestral knowledge, it strengthens cultural identity and fosters feelings of relevance towards one's own ethnic group. However, the “home outside” application perspective still has shortcomings because it is not applied throughout the National Educational System and there are no relevant curricular updates. In conclusion, Afro-Ecuadorian ethno-education is a proposal that must continue to be strengthened “home inside” and “home outside", for this, the training, awareness, and formation of the entire educational community are of great relevance for its real empowerment.
Keywords: Español; Afro-Ecuadorian ethno-education; cultural relevance; ancestral knowledge; cultural identity